(untitled) (Journal of Health Informatics in Africa, 2024)
The Journal of Health Informatics in Africa (JHIA) only publishes original, high quality research papers focusing on the use of information and ICTs in the healthcare sector in Africa. To ensure originality a Turnitin report is obtained for each submission before being assigned to reviewers. Only submissions with a Turnitin similarity index below 15% are accepted for review. Submission with a higher similarity index is immediately rejected. Authors are thus urged to ensure that their submissions are original and that it has not been published elsewhere before submission is made to JHIA. Once a submission is accepted for review it passes through a rigorous double-blind review process that either results in a rejection or acceptance. Most submissions that are accepted are subject to a second round of review. Authors are tasked to revise the paper based on the reviewer feedback and re-submit it for a second round of review by the same reviewers. Only once the reviewers and editorial team are satisfied with the revisions are the paper then formally accepted for publication. To attest to the rigorous review process this issue comprises of only two papers: • Gumede and Dyers presents a cross-sectional evaluation of the user experience of an Electronic Medical Record (EMR) in the public health sector of the Western Cape in South Africa. The user experience of the EMR is evaluated in terms of it’s pragmatic- and hedonic qualities. • Mutunhu, Chipangura, and Singh explores opportunities for quantified-self technology in diabetes self-care through a systematic literature review. Four opportunities namely monitoring, adherence, reduced cost, and data collection and sharing are identified. I would like to extend a very special thank you to the editorial team, authors, and peer-reviewers that made this issue possible. I encourage readers active in health informatics research to make contact with me to become reviewers for JHIA. We rely on the expertise of experienced researchers to ensure the publication of high-quality research. Nicky Mostert March 2024